Pre-service Accounting Teachers’ Perceptions and Experiences of Mathematics Anxiety - Mkhize, Msizi Vitalis (Language, Literature and Education: Research Updates Vol. 2, 2025)
Mathematics is a subject that causes anxiety in many students. Mathematics is crucial to the study of accounting. It has been observed that students who appear to be capable in mathematics but are so apprehensive about it, that they are rendered helpless when it comes to independently performing accounting tasks, tests, or examinations. The purpose of the study was to explore pre-service teachers’ perceptions and experiences of mathematics anxiety as it relates to the study of accounting. The Fennema-Sherman Mathematics Anxiety Scale, with established reliability and validity, was applied. A cross-sectional data set containing demographic details and attitudes towards mathematics anxiety was collected and quantitative responses of 255 first-, second-, and third-year pre-service teachers were analysed. In addition, semi-structured interviews with 18 pre-service accounting teachers, 6 from each level, were conducted. A sequential explanatory mixed methods design was employed. Data were analysed using the Statistical Package for Social Sciences for quantitative data, and semi-structured interviews were analysed thematically. The study revealed that the Mathematics Anxiety Scale score is slightly above neutral and affects students’ confidence in doing accounting calculations. Qualitative results revealed that even mathematically competent students are not free from mathematics anxiety. The correlation between mathematics anxiety score and achievement in accounting modules revealed that the higher the agreement that mathematics is useful, the better students perform, and the higher the agreement that they are not anxious, the better they perform in accounting 320. Mathematics anxiety affects and influences the way students do accounting calculations and the way they learn accounting calculations. Accounting lecturers should identify the accounting students who have high mathematical anxiety and who show a defeatist attitude during the accounting class. Remedial psychological assistance could be given to these students, or alternatively, lecturers should revise their presentation methods to try to shift the students from this kind of attitude.